Nucleotides bearing aminophenyl- or aminonaphthyl-3-methoxychromone solvatochromic fluorophores for the enzymatic construction of DNA probes for the detection of protein-DNA binding - Matyašovský, Ján; Tack, Laure; Palágyi, Attila; Kuba, Miroslav; Pohl, Radek; Kraus, Tomáš; Güixens-Gallardo, Pedro; Hocek, Michal (Organic & biomolecular chemistry, 2021)
We designed and synthesized nucleosides bearing aminophenyl- or aminonaphthyl-3-methoxychromone fluorophores attached at position 5 of cytosine or thymine and converted them to nucleoside triphosphates. The fluorophores showed solvatochromic fluorescence with strong fluorescence at 433-457 nm in non-polar solvents and very weak fluorescence at 567 nm in alcohols. The nucleosides and nucleotides also showed only negligible fluorescence in alcohols or water. The triphosphates were substrates for DNA polymerase in the enzymatic synthesis of modified DNA probes that showed only very weak fluorescence in aqueous buffer but a significant light-up and blue shift were observed when they interacted with proteins (histone H3.1 or p53 for double-stranded DNA probes or single-strand binding protein for single-stranded oligonucleotide probes). Hence, nucleotides have good potential in the construction of DNA sensors for studying protein-DNA interactions. The modified dNTPs were also transported into cells using a cyclodextrin-based transporter but they were not incorporated into the genomic DNA.
Keywords: Protein Binding; Proteins; Enzymes; DNA; fluorescence; fluorescenční barviva; vazba proteinů; Fluorescent Dyes; Chromones; chromony; proteiny; DNA Probes; Nucleotides; nukleotidy; enzymy; DNA sondy; Fluorescence